The importance of considering psychological aspects in the process of training philology students - Volkova, Liudmyla Viktorivna; Chorna, Alona Ihorivna (Національний університет «Острозька академія», 2024)
The article is devoted to a comprehensive analysis of the psychological readiness of philology students to master professional foreign language communication, which is an integral part of their pedagogical and methodological training. The study focuses on the relationship between motivational, cognitive, emotional-volitional and cultural components that form the ability of students to successfully interact in a foreign language environment. Key psychological barriers are highlighted, such as anxiety, fear of mistakes, low self-esteem and insecurity, as well as problems of intercultural communication that arise due to insufficient understanding of cultural characteristics. When considering psychological readiness in the context of philological education, it should be taken into account that it includes both a personal component (the desire to improve one’s knowledge and ability to reflect) and a professional component – an orientation towards the application of foreign language skills in teaching or translation activities. The article examines in detail the pedagogical conditions that contribute to the development of psychological readiness, including interactive forms of learning, international language projects, the creation of a language environment and the involvement of digital technologies. The role of psychological support and motivational training in overcoming students’ fears and anxiety is separately analyzed. The authors also address the problems of integrating theoretical and practical knowledge, offering recommendations for improving the educational process. The paper also proposes a number of practical recommendations that will contribute to the formation of this readiness, including the use of interactive methods, an individualized approach and the latest technologies. The authors draw attention to the problems faced by future philologists and suggest ways to solve them through the adaptation of teaching methods, the introduction of new technologies and the development of intercultural competence. The practical aspect is presented in the form of recommendations for educational institutions. The research materials are based on the results of modern scientific works, empirical research and practical experience. The article may be useful for teachers of higher education institutions, methodologists, researchers in the field of education and students who seek to increase the level of professional foreign language competence.

Стаття присвячена комплексному аналізу психологічної готовності студентів-філологів до опанування професійного іншомовного спілкування, що є невід’ємною складовою їхньої педагогічної та методичної підготовки. У дослідженні акцентовано увагу на взаємозв’язку мотиваційних, когнітивних, емоційно-вольових і культурних компонентів, які формують здатність студентів успішно взаємодіяти в іншомовному середовищі. Висвітлено ключові психологічні бар’єри, такі як тривожність, страх помилок, низька самооцінка та невпевненість, а також проблеми міжкультурної комунікації, що виникають через недостатнє розуміння культурних особливостей. Розглядаючи психологічну готовність у контексті філологічної освіти, слід враховувати, що вона включає як особистісний компонент (бажання вдосконалювати свої знання і здатність до рефлексії), так і професійний компонент – орієнтацію на застосування іншомовних навичок у викладацькій або перекладацькій діяльності. У статті детально розглянуто педагогічні умови, які сприяють розвитку психологічної готовності, включно з інтерактивними формами навчання, міжнародними мовними проєктами, створенням мовного середовища та залученням цифрових технологій. Окремо проаналізовано роль психологічної підтримки та мотиваційних тренінгів у подоланні страхів і тривожності студентів. Автори також звертаються до проблем інтеграції теоретичних і практичних знань, пропонуючи рекомендації для вдосконалення навчального процесу. У роботі також запропоновано низку практичних рекомендацій, що сприятимуть формуванню цієї готовності, включно з використанням інтерактивних методик, індивідуалізованого підходу та новітніх технологій. Автори звертають увагу на проблеми, з якими стикаються майбутні філологи, та пропонують шляхи їх вирішення через адаптацію методик навчання, впровадження новітніх технологій та розвиток міжкультурної компетентності. Практичний аспект викладений у формі рекомендацій для освітніх закладів. Матеріали дослідження спираються на результати сучасних наукових праць, емпіричних досліджень і практичного досвіду. Стаття може бути корисною для викладачів закладів вищої освіти, педагогів-методистів, дослідників у сфері освіти та студентів, які прагнуть підвищити рівень професійної іншомовної компетентності.
Keywords: motivation; cognitive development; emotional-volitional stability; intercultural competence; interactive methods; digital technologies; мотивація; когнітивний розвиток; емоційно-вольова стабільність; міжкультурна компетенція; інтерактивні методи; цифрові технології